THERMALLY STABLE DYSPROSIUM DOPED ZINC-SODIUM-TELLURITE GLASSES: ABSORPTION AND EMISSION PROPERTIES ENHANCEMENT - Badamasi, S.; Tanko, Y. A.; Yamusa, Y. A.; Garba, N. N.; Najamuddeen, Musa M. (FUDMA JOURNAL OF SCIENCES, 2020)
Tellurium dioxide among the numerous glass formers have been of interest to researchers due to its promising characteristics. Consequently, absorption and emission are among the most paramount features of glasses applicable in lasers and other optical devices, but there are not much report on absorption and emission properties of Zinc-Sodium-Tellurite Dysprosium doped glasses. Series of dysprosium (Dy3+) ions doped zinc-sodium-tellurite glass having composition (65-x)TeO2-25ZnO-10Na2O-xDy2O3 (0 ≤ x ≤ 2.5 mol%) were prepared using melt-quenching method. Transparent and thermally stable glass samples were characterized via UV-Vis-NIR absorption, photoluminescence (PL), and Fourier transform infrared (FTIR) spectroscopy. Density and molar volume of prepared glass system were found to be in the range of 5.334-5.366 gm-3 and 24.425-25.273 cm3mol-1, respectively. FTIR spectra exhibited various bonding vibrations corresponding to glass network structures and units. UV-Vis-NIR spectra revealed seven absorption peaks centred at 450, 752, 801, 901, 1095, 1281, and 1687 nm which were assigned to the transitions from the ground state to the excited levels such as6H15/2 →4F9/2, 6H15/2 →6F3/2, 6H15/2 →6F5/2, 6H15/2 →6F7/2, 6H15/2 →6H7/2, 6H15/2 →6F11/2, and 6H15/2 →6H11/2 of Dysprosium Dy3+ ions, respectively. Room temperature PL spectra displayed three significant peaks centred at 497, 588, and 675 nm, which were allocated to the transitions from 4F9/2 excited state to the 6H11/2, 6H13/2, and 6H15/2 states, respectively. Present optimized glass composition may be potential for the development of solid state lasers and photonic devices.